Critical Discourse Analysis Using Norman Fairclough Model on MediaIndonesia.com Merdeka Belajar Episode 26 - Fitriana, Rina; Hidayani, Selnistia (Program Studi Magister Tadris Bahasa Inggris UIN Sultan Maulana Hasanuddin Banten, 2024)
This research aims to find out how the news construction about the Merdeka Belajar policy Episode 26 released by the Ministry of Education, Culture, Research and Technology was packaged using Nourman Fairclough's critical discourse analysis. This research method uses qualitative research analysis with the scalpel of critical discourse analysis developed by Norman Fairclough. The research data used is the MediaIndonesia.com news text published on August 29 2023. The research results reveal that critical discourse analysis emphasizes discourse as a form of interaction through the use of spoken and written language as a form of social practice. Social practice in critical discourse analysis is related to events from a reality and social structure. The role of the media cannot be separated from ideological practices, meaning that the media presents news using certain constructions to attract readers' interest. MediaIndonesia.com presents emerging realities with the character of selecting titles and discourse that are appropriate to the news context. The language used in news texts is packaged lightly, briefly and easily understood by the wider public.